Challenging Health Service Delivery Models to Improve Access to Physical Therapy in Rural, Remote and Northern Communities - Smith, Liris P. R. (Frontiers in Rehabilitation Sciences, 2022)
Effective rural, remote and northern physical therapy services are an important component of health care. Providing these services with limited financial and human resources can present many challenges. Indigenous communities also have unique needs that must be considered when providing health care. Most current service delivery models are based in Western medicine practices and most often, do not account for the local, political, cultural and spiritual needs of communities. In this perspective article, I discuss the challenges of providing these services in rural Yukon to many small First Nation communities. Relationship building is paramount to effective and meaningful health care programs, and this means a change in current practice approaches. We need to challenge the delivery models and be open to other ways of knowing, beyond the Western biomedical approach that is the foundation of our profession. It is imperative that physical therapists, health care providers and funders seek new and innovative ways to provide services to the rural, remote and northern communities while ensuring a culturally humble approach.